2023
DOI: 10.1002/jor.25532
|View full text |Cite
|
Sign up to set email alerts
|

Tendon cell and tissue culture: Perspectives and recommendations

Abstract: The wide variety of cell and tissue culture systems used to study and engineer tendons can make it difficult to choose the best approach and “optimal” culture conditions to test a given hypothesis. Therefore, a breakout session was organized at the 2022 ORS Tendon Section Meeting that focused on establishing a set of guidelines for conducting cell and tissue culture studies of tendon. This paper summarizes the outcomes of that discussion and presents recommendations for future studies. In the case of studying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…First, tissue explant models do not perfectly mimic the in vivo environment. While they do maintain native cell–cell and cell–matrix interactions (in contrast to isolated cell in vitro models), 44 explant culture still alters cell phenotypes and cyclic tensile loading does not perfectly mimic the complicated loading environment of the ACL in vivo 28 . Indeed, we found that the expression of nearly all genes was different in explant culture compared to freshly harvested controls (Supporting Information: Figure ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…First, tissue explant models do not perfectly mimic the in vivo environment. While they do maintain native cell–cell and cell–matrix interactions (in contrast to isolated cell in vitro models), 44 explant culture still alters cell phenotypes and cyclic tensile loading does not perfectly mimic the complicated loading environment of the ACL in vivo 28 . Indeed, we found that the expression of nearly all genes was different in explant culture compared to freshly harvested controls (Supporting Information: Figure ).…”
Section: Discussionmentioning
confidence: 88%
“…While they do maintain native cell-cell and cell-matrix interactions (in contrast to isolated cell in vitro models), 44 explant culture still alters cell phenotypes and cyclic tensile loading does not perfectly mimic the complicated loading environment of the ACL in vivo. 28 Indeed, we found that the expression of nearly all genes was different in explant culture compared to freshly harvested controls (Supporting Informa- loading. Second, while we selected our loading levels based on in vivo measurements of ACL loading, 31,36 it is possible that the same stress levels cause different amounts of tissue damage for male and female ACLs given that female human ACLs have inferior mechanical properties.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Breakout discussions on several topics were had at the conference and these discussions were summarized in five review/perspective papers in this issue. These topics included tendon cell lineage, 1 tendon cell culture and bioreactors, 2 methods for biomechanical assessment, 3 methods for histological assessment, 4 and preclinical animal models 5 . We have also included 17 original research papers from members of the Tendon Section and colleagues, most of which were based on research that was presented at the conference.…”
mentioning
confidence: 99%